Compare the Accuracy of IOL Power Calculations Using Ultrasound Biometry and Partial Coherence Laser Interferometry based Optical Biometry - Dhan Singh Meena; Himani Sukhadia; Sanjay Goyal; Vaibhav Kumar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aims: To compare the accuracy of IOL power calculations using ultrasound biometry and partial coherencelaser interferometry based optical biometryMaterial and Methods: All cases of cataract with no other pathology involved presenting to, ophthalmologydepartment at RNT Medical College and Hospital, Udaipur from august 2018 to December 2019.The patientsare divided into two group 1st group IOL power calculated by optical biometer and 2nd group IOL powercalculated by ultrasound biometry.Results: Significant p-value (0.01) was observed between Group 1 and Group 2 among pre operative andpost-operative VS patients.Conclusion: optical biometry with the AL scan (Nidek) proved to be slightly more accurate than ultrasoundbiometry for IOL power calculation